Control of a Single-Phase Islanded Microgrid Based on Virtual Oscillator Control Enhanced With Power Limitation and Robust Distributed Secondary Control - Ronald Musona; Ioan Serban (IEEE, 2025)
Virtual oscillator control (VOC) has emerged as an alternative solution for controlling parallel connected inverters in microgrids (MGs) due to its self-synchronization and advanced control capabilities. To enhance the operations of VOC-based inverters, this article implements a power limitation controller that dispatches power according to the operating conditions and the primary source availability. Therefore, this mechanism allows the inverter to adapt to the intermittent nature of renewable energy sources and the operational constraints of batteries. The controller can limit both active and reactive power to specified setpoints. When an inverter reaches its power limit, the others that are not restricted by the power limitation take on the extra load. On top of VOC, a robust distributed secondary control was developed to restore the MG voltage and frequency. The controller uses the local frequency and voltage and the powers from the neighboring nodes obtained through a sparse communication network. Last, as part of a single-phase MG configuration, single-phase inverters generate a second-order current component in their dc-link that needs to be restricted from flowing to the dc source. To address this issue, this article implements a minimalist active power decoupling method adapted to the VOC inverter. Extensive simulations and experiments were conducted to validate the operation of the proposed system.